Cyclic performance of RC beam-column joints with mechanical or forging (GPW) splices; an experimental study. (December 2020) - Kheyroddin, Ali; Dabiri, Hamed
Abstract: Beam-column joints affect the performance of structures remarkably, therefore, finding an appropriate method for their construction has always been one of the major concerns of researchers. In the present study, the influence of incorporating mechanical and forging (gas pressure welding) splices in longitudinal reinforcement bars of beams on the cyclic performance of RC beam-column joints is evaluated experimentally. Totally five RC joints with non-spliced, mechanically (threaded couplers) spliced and forging spliced bars were examined under axial and cyclic loads applied to columns and beams, respectively. Crack propagation of specimens are analyzed and load-drift hysteresis curves are provided as test outputs. Moreover, the influence of the splice method and number of spliced bars on joints' behavior is assessed in terms of seismic parameters including displacement ductility, stiffness and cumulative absorbed energy. Results showed that forging splices can be considered as an efficient and reliable method for bar splicing and mechanical splices might affect joints' behavior significantly.